The Potential for Dark Tourism in Kazakhstan: An Overview of the Former Concentration Camps - Aigerim Assylkhanova; Kamshat Mussina; Gyula Nagy; Samalgul Nassanbekova; Zhaxat Kenzhin; Lajos Boros (Tourism and Hospitality)
The concept of dark tourism has attracted considerable attention in recent years. The studies in this field examine the convergence of tourism and morbidity. The research problem lies in understanding the complex dynamics between the preservation of historical sites associated with Kazakhstan’s former gulags and their role in the emerging dark tourism sector. This paper explores the tourist significance of the former gulags in Kazakhstan through the analysis of interviews, legislation texts and policy documents, and data on visitor numbers. Our aim is to illuminate the historical importance for tourism, educational value, and stakeholders associated with the preservation and promotion of these destinations. The analysis revealed the various and sometimes conflicting interests and concerns of the stakeholders, including tourists, local communities, government institutions, and the private sector. The analysis of statistical data provided valuable information on visitor demographics, preferences, and trends in the Karlag and Alzhir museums. These data highlighted the role of educational institutions and demonstrated the adaptability of museums in difficult times such as the COVID-19 pandemic. During the formation of future policies, effective collaboration with stakeholders, responsible tourism practices, capacity building, and sustainable marketing strategies are essential to the ethical and sustainable management of dark tourist sites. Thus, stakeholders can ensure that dark tourism continues to evolve in a way that respects historical integrity and benefits local communities, while contributing to the broader goals of education and commemoration.